مقطوعات أغانى الأطفال "الروك جاز" على آلة البيانو عند آرماندو أنتوني كوريا - باشا، سلوى حسن محمد محمود (جامعة حلوان - كلية التربية الفنية, 2011)
الجاز هو صيغة من صيغ فنون الموسيقى تتميز بأنغام البلوز وأداء السنكوب، السوينج، التيمات اللحنية ذات السؤال والجواب، التعدد الإيقاعي والإرتجال. جذور موسيقى الجاز نشأت من ثقافة المجتمعات الأمريكية الأفريقية بالقرب من بداية القرن العشرين من قبل عام 1920، كما يطلق عليها أنها شعبية دولية لما لموسيقى الجاز من تأثير عميق على انتشار الأنماط الموسيقية الأخرى في جميع أنحاء العالم لأن موسيقى الجاز تتميز بالتطوير المستمر والمستوحى من غرب أفريقيا والتعبيرات الموسيقية في تقاليد الموسيقى الأمريكية الأفريقية، في البلوز الشعبي والراج تايم، إن موسيقى الجاز تتميز بإظهار عمق العاطفة الفردية في تاريخ الموسيقى الغربية. المؤلفات الموسيقية لآلة البيانو عديدة متنوعة الأسلوب والطابع في مختلف العصور الموسيقية باعتبارها الآلة الرئيسة الكاملة الميلودية والهارمونية للتأليف والأداء الموسيقي الأمثل في تآلف وإبهار من خلال مختلف الصياغات الموسيقية. فالمؤلف الموسيقي "شيك كوريا" قام بتأليف العديد من المؤلفات الموسيقية لآلة البيانو، لذا رأت الباحثة أن دراسة مؤلفة مقطوعات أغاني الأطفال "عشرون مقطوعة ED 7254" طبعة سكوت Schott لآلة البيانو سوف تكون بمثابة بداية جيدة لفتح مجال الأداء لأنواع عديدة ومتنوعة من المؤلفات الموسيقية الخاصة بموسيقى الجاز عامة والروك جاز (فيوجن) خاصة التي تساهم في زيادة الثقافة والقدرة الموسيقية المعرفية المهارية الخاصة بموسيقى الجاز للطلاب. Jazz is the version of the music Arts features with blues s tunes and syncope performance, swing, melodic themes of the question and answer, multi-rhythmic and improvisations. The roots of jazz originated from a culture of communities, African-American near the beginning of 20 century, before 1920, called it international popularity as a jazz from a profound impact on the spread of musical styles of other throughout the world, because jazz is characterized by continuous development and inspired by the West Africa and expressions in the musical traditions of African-American music,Blues People in Rag Time,said that jazz is characterized by showing the depth of individual s emotion in the history of Western music. Musical compositions for piano in many different style and character in various musical eras as the main instrument ,full of melodic /harmonic of the written and performance in perfect harmony, in composing music that impress through various musical formulations. Music compose r "Chick Corea” composed numerous musical compositions for piano. so felt the researcher that the study of composed pieces of children’s songs "Twenty broken ED 7254 edition of Scott for the piano will be a good start to open up the performance for many types and variety of musical compositions for jazz in general and rock Jazz (Fusion), especially that contribute to increase the musical cultureand ability cognitive skill for jazz students. \ Tags: musical times (twentieth century)Jazz- Jazz Rock Band "Jazz Fusion"-the style of Armando Anthony Corea"Chick Corea" Children Songs "Twenty broken ED 7254" Schott piano edition.
Keywords: موسيقي الروك; البيانو (آلة موسيقية); أغانى الأطفال; موسيقي الجاز